2014
DOI: 10.1007/s00256-014-1869-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring cartilage damage in gout using 3-T MRI: distribution and associations with joint inflammation and tophus deposition

Abstract: Magnetic resonance imaging can be used to investigate cartilage in gout. Cartilage damage was relatively uncommon, focal, and associated with bone erosions, tophi and synovitis, but not bone oedema. This emphasises the unique pathophysiology of gout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 25 publications
1
26
0
1
Order By: Relevance
“…Analysis of MRI scans has shown that cartilage damage is predominantly focal and closely related to sites of tophus deposition [49]. In this same study, bone erosions were associated with cartilage destruction, and tophus infiltration into bone was accompanied by damage to the overlying cartilage.…”
Section: Structural Consequences Of Tophaceous Goutmentioning
confidence: 80%
“…Analysis of MRI scans has shown that cartilage damage is predominantly focal and closely related to sites of tophus deposition [49]. In this same study, bone erosions were associated with cartilage destruction, and tophus infiltration into bone was accompanied by damage to the overlying cartilage.…”
Section: Structural Consequences Of Tophaceous Goutmentioning
confidence: 80%
“…We recently developed an MRI scoring system to assess cartilage damage at the wrist in gout . Although the wrist is not a typical clinical site for acute gout attacks, we have found a high level of clinical and subclinical involvement in the Maori and Pacific Island patients who present frequently to rheumatology clinics in Auckland, New Zealand and have severe, disabling gout .…”
Section: Introductionmentioning
confidence: 97%
“…Molecular imaging can provide molecular information on the underlying biochemical and inflammatory processes, that is complementary to anatomical imaging. Development of metal plasmonic nanoparticles for MRI25 allows using MRI also for molecular imaging in addition to its use for anatomical imaging. Other molecular probes being developed for molecular arthritis imaging include fluorescence and near-infrared labelled probes26 for optical imaging or radioisotopes labelled probes for scintigraphy, PET or SPECT14.…”
Section: Discussionmentioning
confidence: 99%